The Role of The Church in Fighting Against Domestic Violence in Bufunda Division Ibanda Municipality. - Nahwera, Justine (Kabale University, 2024)
The study aimed to assess the role of the church in fighting against domestic violence in the Bufunda division of Ibanda municipality.